2013
DOI: 10.1007/s10637-013-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, mechanism of action and sensitivity profile of fluorocyclopentenylcytosine (RX-3117; TV-1360)

Abstract: A novel cytidine analog fluorocyclopentenylcytosine (RX-3117; TV-1360) was characterized for its cytotoxicity in a 59-cell line panel and further characterized for cytotoxicity, metabolism and mechanism of action in 15 additional cancer cell lines, including gemcitabine-resistant variants. In both panels sensitivity varied 75-fold (IC50: 0.4- > 30 μM RX-3117). RX-3117 showed a different sensitivity profile compared to cyclopentenyl-cytosine (CPEC) and azacytidine, substrates for uridine-cytidine-kinase (UCK). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 47 publications
1
60
0
Order By: Relevance
“…Non-solid tumor cell lines CCRF-CEM (Lymphoblastic leukemia) and U937 (Leukemic monocyte lymphoma) were cultured in RPMI1640 medium (Lonza) supplemented with 10% fetal bovine serum and 20 mM HEPES. The sources of the cell lines have been described earlier [3]. Cells were maintained in an experimental growth phase for all experiments and were tested negative for mycoplasma.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Non-solid tumor cell lines CCRF-CEM (Lymphoblastic leukemia) and U937 (Leukemic monocyte lymphoma) were cultured in RPMI1640 medium (Lonza) supplemented with 10% fetal bovine serum and 20 mM HEPES. The sources of the cell lines have been described earlier [3]. Cells were maintained in an experimental growth phase for all experiments and were tested negative for mycoplasma.…”
Section: Methodsmentioning
confidence: 99%
“…Cytidine analogs, a subclass of nucleoside analogs that are inserted into RNA and DNA replacing cytidine, are used to treat a wide variety of cancer types. Examples of successful cytidine analogs in anti-cancer applications are cytarabine and gemcitabine [2, 3], the latter drug is predominantly used for treatment of patients with non-small cell lung cancer (NSCLC) [4]. Nevertheless, the inter- and intra-tumor heterogeneity can imply for resistance to drugs in patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, RX-3117 can act as an effective demethylating agent by inhibiting DNA methyltransferase (DNMT). Interestingly, unlike gemcitabine, RX-3117 is a poor substrate for cytidine deaminase (CDA) as shown by Peters et al in their in vitro studies in the U397 cell line simultaneously treated with RX-3117 and tetrahydrouridine (THU), an inhibitor of CDA enzyme [69]. A first-in-human trial of RX-3117 in patients with solid tumours has been completed and demonstrated encouraging evidence of the single agent safety and tolerability [71].…”
Section: Other Pyrimidine-based Anticancer Fluorinated Nucleoside Anamentioning
confidence: 99%